WILLINGNESS TO COMMUNICATE IN ENGLISH: A CASE STUDY OF INDONESIAN UNIVERSITY STUDENTS - ,, Muamaroh; Prihartanti, Nanik (Kajian Linguistik dan Sastra, 2013)
This paper describes Indonesian university studentâs willingness to actively engage in English language learning and their self-reported anxiety levels. The objectives of this study are to describe the willingness of Indonesian students to communicate in English, and to explain the relationship between anxiety and willingness to communicate in English. The participants of this study are 426 students of Bachelorâs Degree in Muhammadiyah University of Surakarta (UMS). The instruments used to gather data are questionnaire and interview. Quantitative data is analized using regression analysis (ANAREG) and qualitative data is analyzed using descriptive analysis. The results of the study show that their willingness to communicate in English is very low (scored 14.21 on WTC scale) while their anxiety is at moderate level (scored 39.66 on FLCAS scale). Only half of the students (51%) have low willingness to communicate in English. More than half (68%) of students indicate that their language anxiety influences their willingness to communicate in English, while 12% of them does not show that their anxiety influence their linguistic behavior. This study finds a significantÂ  elationship between language anxiety and willingness to communicate.